Literature Riview: Pengembangan Modul Berbasis Project Based Learning (PjBL) untuk Meningkatkan Pemahaman Konsep dan Keterampilan Kolaborasi Siswa - Dea Agustika; Tri Ariani (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
The purpose of this article is to examine the effectiveness of learning modules developed using the Project-Based Learning (PjBL) approach in improving students' conceptual understanding and collaboration skills. From a total of 200 articles collected, 50 articles were selected from Google Scholar, Sinta, and Spiece as the main sources and analyzed to identify module development patterns, implementation strategies, and learning outcomes. The results of the review show that PjBL-based modules are able to strengthen students' conceptual understanding through project activities, authentic problem solving, and product development relevant to the learning context. A number of studies report an increase in academic scores and learning completeness after using these modules. In addition, PjBL also contributes to improving collaboration skills, as students are actively involved in group work, discussions, role sharing, and joint decision making. Several studies state that students respond positively to collaborative activities during the implementation of PjBL. Various forms of modules, whether printed, digital, or those that integrate the STEAM approach, are considered feasible and effective in increasing student participation. Overall, the review results indicate that the development of PjBL-based modules has strong potential to improve students' conceptual understanding and collaboration skills.